Metabolic Response of Pelvic and Para-Aortic Lymph Nodes During Radiotherapy for Carcinoma of the Uterine Cervix: Using Positron Emission Tomography/Computed Tomography. Issue 4 (1st April 2011) - Yoon, Mee Sun; Nam, Taek-Keun; Chung, Woong-Ki; Jeong, Shin Young; Ahn, Sung-Ja; Nah, Byung-Sik; Song, Ju-Young; Jeong, Jae-Uk
Abstract : Objectives: We evaluated the metabolic response of lymph nodes (LNs) using consecutive 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography (PET/CT) and correlated the metabolic response with the volumetric response measured by consecutive CT. Methods: Twenty-two patients with cervical cancer that had positive LNs underwent preradiotherapy (pre-RT) and inter-RT PET/CT. The metabolic response of the LNs was assessed quantitatively and semiquantitatively by measurement of the maximal standardized uptake value. All patients underwent inter-RT CT simulation after 45 Gy to the whole pelvis and inter-RT PET/CT scans after median 63 Gy to the gross LNs. Results: A total of 48 pelvic and para-aortic LNs were found on the pre-RT PET/CT. The mean maximal standardized uptake value of nodal disease decreased from the pre-RT of 5.2 (SD, 3.1; range, 1.8-15.6) to the inter-RT of 1.1 (SD, 2.1; range, 0-11.1). Classifying the metabolic response of all 48 nodal lesions on the inter-RT PET/CT, 38 had a complete metabolic response. The initial volume of LNs had no correlation with the metabolic response ( r = 0.194, P = 0.186). The metabolic response between the pre-RT PET/CT and inter-RT PET/CT was significantly associated with the volume response between the pre-RT CT and inter-RT CT ( r = 0.314, P < 0.05). However, 18 (38%) LNs showed discrepancy between metabolic response and residual LN volume. Six (27%) patients had modified RT during treatment based on inter-RT PET/CT. Conclusions: We suggest that the PET/CT can be a useful tool for the evaluation of the interim response of the LNs and aid in selecting patients that need further treatment. The results showed a significant correlation between the metabolic and volumetric responses during RT, although the anatomical changes of LNs would not always represent the metabolic status.